POSTING KITA (Posyandu Anti Stunting Berbasis Kolaborasi Teknologi Informasi E-Posyandu dan Asuhan Gizi Balita) - Rachmawati, Ervina; Puspitasari, Trismayanti Dwi; Santi, Maya Weka; Lestari, Datik (SEJAGAT : Jurnal Pengabdian Masyarakat, 2024)
Stunting is a condition where a toddler has less length or height compared to age. The prevalence of toddlers with nutritional problems is highest in East Java, namely Jember Regency with a prevalence of stunting (34.9%), wasting (12.7%) and underweight (24.1%). Kemuning Lor Village, Arjasa District, Jember Regency has quite high cases of nutritional problems among toddlers, reaching 80 toddlers, so efforts are needed to reduce these nutritional problems. The community service team has created the E-Posyandu Kelor System which must be implemented continuously by all posyandu in Kemuning Lor village to carry out early detection of stunting. Apart from that, there is a need for quality nutritional care to meet the nutritional needs of toddlers. This service activity took place at the Kemuning Lor village hall and was attended by health cadres from 11 posyandu in Kemuning Lor village and accompanied by the village midwife. The activities carried out include 1) training of Posyandu cadres regarding the operation of the e-Posyandu kelor, 2) assisting cadres in implementing Posyandu data recording into the e-Posyandu kelor application, and 3) training of posyandu cadres in making MP-ASI and PMT with diversification of local food ingredients. After the service activities, there was an increase skills in making MP-ASI and cadres were able to record posyandu data on the e-posyandu kelor application. Furthermore, cadres are expected to record posyandu data periodically on the e-posyandu kelor application and make quality MP-ASI/PMT to reduce the incidence of stunting